Agents, Spolia and Transculturality in the Post-Roman Mediterranean - Elices Ocón, Jorge (Medieval encounters, 2025)
This paper focuses on the agents of spoliation: these were individuals who relocated and appropriated ancient spolia within a new context. It examines literary and archaeological evidence from late antiquity to the late Middle Ages and from Christian, Islamic, and Jewish contexts, focusing on how antiquity was perceived and mediated by individuals who, despite being mentioned and portrayed in literary accounts based chiefly on topoi, in fact played a central role in the process of spoliation. This paper adopts a diachronic, comparative, and transregional approach in order to show that these agents shaped spoliation as a transcultural phenomenon, acting as mediators and cultural brokers. They shared strategies of reuse that were operative across communities, providing spolia with new values and meanings.